Battle for truth: poetic interruptions into symbolic violence through sound portraits. (28th February 2019) - Baker, Alison
Abstract : Purpose: Racialised misrepresentation circulated en masse can be understood as a form of symbolic and cultural violence. Such misrepresentations create a dominant cultural narrative that positions people of African background as violent and troubled and therefore incompatible with Australian society. Young people from various groups have been using arts-for-social-change to challenge and dismantle these imposed misrepresentation and reconstruct narratives that reflect their lived experiences. The purpose of this paper is to explore sound portraits, both the process and product, by tracing the journey of New Change, arts collective comprised of young women of African heritage, who have been pushing for social change. Design/methodology/approach: This collaborative research mobilises arts methodologies, bringing together sound arts, audio documentary and narrative research methods. Data gathering included arts artefacts and interviews with the young women and sound recordings from news media to craft a sound portrait entitled "Battle for truth". Findings: Battle for Truth is a sound portrait that serve as the findings for this paper. Sound portraits privilege participants' voices and convey the complexity of their stories through the layering of voices and other soundscapes. This sound portrait also includes a media montage of racialised misrepresentation. Social implications: Through their restorying, sound portraits are a way to counter passive and active forgetting and wilful mishearing, creating a space in the public memory for polyphonic voices and stories that have been shutout. Sound portraits necessitate reflexivity and dialogue through deep listening, becoming important sites for reimagining possibilities for social change and developing new activist avenues. Originality/value: This paper brings together sonic methods, liberation arts and social justice perspectives to attend to power, race, gender and voice.